School Principals’ Strategies in Improving Primary School Teachers Performance: Literature Review Study - Dewi, Fadilah; Maiysaroh, Maiysaroh; Ubaidillah, Aan Fardani (International Journal of Business, Law, and Education, 2024)
This study aims to explore the strategies employed by school principals to enhance the performance of primary school teachers by conducting a comprehensive analysis of existing literature, highlighting effective strategies, implementing these strategies at the primary school level, and evaluating their impact on teacher performance. The research findings are expected to provide valuable insights for school leaders and education stakeholders regarding effective strategies, their implementation, and their effects on teacher performance. The literature review method is utilized to gather and analyze information from various relevant sources. It is hoped that this research will contribute to creating a more supportive educational environment for teacher development, improving overall education standards, particularly at the primary school level, and refining educational practices through the informed implementation of strategies derived from this extensive review, thereby laying a strong foundation for advancing future generations.